2014
DOI: 10.17221/879/2013-pse
|View full text |Cite
|
Sign up to set email alerts
|

Soil chemical properties as affected by tillage and crop rotation in a long-term field experiment

Abstract: Long-term field experiments are important for explaining tillage and rotation effects on soil fertility and to develop sustainable nutrient management strategies. An experiment was established in 1996 in Raasdorf (Austria) on chernozem with four tillage treatments (mouldboard ploughing (MP); no-till; deep conservation tillage and shallow conservation tillage) and two crop rotations. Soil samples were taken in November 2003 from 10 cm soil layers down to 40 cm to assess the effects on pH, carbonate content (CaC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 20 publications
(17 reference statements)
5
33
1
3
Order By: Relevance
“…1A) showing a more homogenous distribution up to a 25 cm depth while pH H 2 O gradually decreased with every sampled layer (except for similar values between a 10-15 and 15-20 cm depth). The vertical gradient of pH CaCl 2 has already been reported for this experiment after seven years (Neugschwandtner et al, 2014). Similarly to pH, an increase in calcium carbonate (CaCO 3 ) was found in this experiment seven years after its initiation (Neugschwandtner et al, 2014), as CaCO 3 buffers the soil pH (Blume et al, 2019).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…1A) showing a more homogenous distribution up to a 25 cm depth while pH H 2 O gradually decreased with every sampled layer (except for similar values between a 10-15 and 15-20 cm depth). The vertical gradient of pH CaCl 2 has already been reported for this experiment after seven years (Neugschwandtner et al, 2014). Similarly to pH, an increase in calcium carbonate (CaCO 3 ) was found in this experiment seven years after its initiation (Neugschwandtner et al, 2014), as CaCO 3 buffers the soil pH (Blume et al, 2019).…”
Section: Resultssupporting
confidence: 81%
“…The aim of this study was to assess the influence of four different soil tillage systems and two crop rotations on basic soil chemical parameters in soil layers fifteen years after establishing a static field trial on a Chernozem in eastern Austria. Several soil characteristics which were assessed in 2003, seven years after the start of the experiment, have been reported earlier by Neugschwandtner et al (2014).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Lack of mixing is most likely also the driver for topsoil nutrient accumulation. A trend towards decreased SOC and nutrient stocks in deeper soil layers as found by Luo, et al 35 and Neugschwandtner, et al 37 could not be found in this trial. With an average of 45% clay containing mainly illites, but also smectites and vermiculites, it is most likely that clay minerals contributed to SOC stabilisation in our case.…”
Section: Discussioncontrasting
confidence: 54%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ stratification with reduced tillage was found for SOC stocks until 50 cm soil depth 34 . Such an increased stratification within the soil profile when comparing conservation with conventional tillage has been widely described for SOC stocks 35,36 and nutrient stocks 37,38 . Luo, et al 35 explained this in terms of a lack of soil mixing that promotes Table 4.…”
Section: Discussionmentioning
confidence: 96%